Nelson Paine, Experimental Theatre, and Puppetry in Ireland, 1942–1952 - Martin G. Molony (Estudios Irlandeses, 2023)
In 1942, a young Dublin architect, Nelson Paine, formed the Dublin Marionette Group on foot of an international re-appraisal of the potential of the puppet theatre as a form of expression. This Group became the nucleus of experimental theatre in the Irish capital and influenced several well-known Irish creative artists over the decade of its existence and beyond. It attracted the involvement of actors, artists and dramatists of the period and performed in professional settings, including eight seasons at the Peacock Theatre and for each of the first four years of the Wexford Opera Festival. This article examines the context of the Group’s formation, its long-forgotten experimental approach, and its considerable contribution to the development of the arts in Ireland.